Implementasi Prinsip Kesetaraan Gender dalam Pendidikan Perspektif Hukum Islam - Nurul Hanifa Azzahra; Tiara Tiara; Kurniati Kurniati (Pusat Riset dan Inovasi Nasional, 2025)
Gender equality in Islamic education in Indonesia is increasingly relevant amid growing awareness of women's roles. Normatively, Islamic law emphasizes al-musāwah (equality) and al-‘adl (justice), but its implementation faces structural and cultural barriers, creating a gap between syariah ideals and practices in educational institutions. This research analyzes the concept of gender equality in Islamic law, identifies legal-social obstacles, and formulates syariah-based solutions for inclusive Islamic education. Employing qualitative library research and descriptive-analytic analysis, the study explores maqāṣid al-syarī‘ah, contextual ijtihād, and khalīfah fī al-arḍ.Findings: Equality is theologically recognized but remains formal; barriers stem from patriarchal fiqh interpretations and cultures that subordinate women. Solutions: Contextual reinterpretation and gender-just policies for equitable Islamic education. The research findings show that although gender equality is recognized in Islamic theological principles, in practice, significant obstacles stem from patriarchal and cultural interpretations of Islamic jurisprudence that place women in a subordinate position. Therefore, contextual reinterpretation and the implementation of more gender-just policies in Islamic education are needed to create a just and equitable learning environment.